Regional competitiveness and analysis of its factors - Volejníková, Jolana; Knězáčková, Radka (Gaudeamus, 2016)
In the context of the set objectives of European Union, competitiveness is considered as one of the most important indicators of economic success of areas. Factors that have influence on the competitiveness form a complex system of interrelated elements. This paper will define the most important factors and it will depict their impact on competitiveness by using dynamic model.
Regionální konkurenceschopnost a analýza jejích faktorů
Keywords: competitiveness; factors of competitiveness; system dynamics model; Faktory konkurenceschopnosti; konkurenceschopnost; model systémové dynamiky